The Power of Habit : Why We Do What We Do, and How to Change - Duhigg, Charles (Cornerstone, 2013)
Takes you to the edge of scientific discoveries that explain why habits exist and how they can be changed. This book brings to life a whole new understanding of human nature and its potential for transformation. It shows, by harnessing this science, we can transform our businesses, our communities, and our lives.